Low-Latitude Atmosphere-Ionosphere Effects Initiated by Strong Earthquakes Preparation Process - Sergey Pulinets (International Journal of Geophysics)
Ionospheric and atmospheric anomalies registered around the time of strong earthquakes in low-latitude regions are reported now regularly. Majority of these reports have the character of case studies without clear physical mechanism proposed. Here we try to present the general conception of low-latitude effects using the results of the recent author’s publications, including also rethinking the earlier results interpreted basing on recently established background physical mechanisms of anomalies generation. It should be underlined that only processes initiated by earthquake preparation are considered. Segregation of low-latitude regions for special consideration is connected with the important role of ionospheric equatorial anomaly in the seismoionospheric coupling and specific character of low-latitude earthquake initiated effects. Three main specific features can be marked in low-latitude ionospheric anomalies manifestation: the presence of magnetic conjugacy in majority of cases, local longitudinal asymmetry of effects observed in ionosphere in relation to the vertical projection of epicenter onto ionosphere, and equatorial anomaly reaction even on earthquakes outside equatorial anomaly (i.e., 30–40 LAT). The equality of effects morphology regardless they observed over land or over sea implies only one possible explanation that these anomalies are initiated by gaseous emanations from the Earth crust, and radon plays the major role.